High affinity agonist binding to cloned 5-hydroxytryptamine2 receptors is not sensitive to GTP analogs. - Szele, F; Pritchett, D (1993)
Agonists for GTP-binding protein (G protein)-coupled receptors are thought to bind with high affinity to the complex of receptor and G protein. Nonhydrolyzable GTP analogs have been shown to disrupt this complex and reduce the binding affinity for many agonists. Antagonists are thought to bind to the receptor whether or not it is coupled to the G protein, and therefore binding remains unchanged in the presence of GTP analogs. The binding of the serotonin 5-hydroxytryptamine (5-HT)2 receptor agonists serotonin (5-HT) and 4-bromo-2,5-dimethoxyphenylisopropylamine is not affected by the presence of GTP analogs when the cloned 5-HT2 receptor is expressed in the 293 human embryonic kidney cell line. The same receptor expressed in mouse NIH3T3 cells is partially sensitive to GTP analogs. Both cell lines have similar proportions of agonist and antagonist binding sites, and agonist stimulation of both cell lines leads to a robust increase in phosphoinositide hydrolysis. Differences in GTP metabolism in 293 cells is not likely to be the cause of the observed difference in inhibition of agonist binding, because the cloned 5-HT1A serotonin receptor expressed in these cells is sensitive to GTP analogs. The GTP-insensitive agonist binding is best explained by the existence of a G protein-receptor complex in 293 cells that is not sensitive to GTP analogs. Such a G protein-receptor complex may explain the fraction of agonist binding in the brain that is not sensitive to GTP analogs.